PAHO Caribbean HIV/STI plan for the health sector 2007 to 2011 : a strategy and plan to support countries in strengthening health systems to maximize the access, quality, and impact of HIV/STI services (PAHO [Washington]US, 2007)
Describes proposed strategies that will be implemented by PAHO and it's administered Caribbean Regional Health Institutions to contribute to health-sector HIV efforts over the next five years.
Keywords: HIV